2017
DOI: 10.1080/14763141.2017.1340508
|View full text |Cite
|
Sign up to set email alerts
|

Do baseball pitchers improve mechanics after biomechanical evaluations?

Abstract: The purpose of this study was to determine how often flaws in pitching mechanics identified from biomechanical analysis are corrected. The biomechanics of 46 baseball pitchers were evaluated twice, with an average of 12 months (range 2-48 months) between evaluations. Pitchers were healthy at the time of both evaluations, competing at the high school, college, minor league or Major League level. After warming up, each participant pitched 10 full-effort fastballs. Automated three-dimensional motion analysis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 24 publications
1
30
0
Order By: Relevance
“…This study is one of only a few that have included training programs, and as such, there is little data to compare. The throwing velocity for our group was comparable to other work, with an average initial pitching velocity of 35.1 ± 1.8 m/s; Fleisig et al (2017a) and Fleisig et al (2017b) had a group of similar amateur pitchers ( n = 25) with an average pitching velocity of 34.2 ± 2.0 m/s. Fleisig et al’s study of underweight and overweight baseball throwing showed variations in arm kinetics, variations in angular velocities, and relatively small changes in body positions.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…This study is one of only a few that have included training programs, and as such, there is little data to compare. The throwing velocity for our group was comparable to other work, with an average initial pitching velocity of 35.1 ± 1.8 m/s; Fleisig et al (2017a) and Fleisig et al (2017b) had a group of similar amateur pitchers ( n = 25) with an average pitching velocity of 34.2 ± 2.0 m/s. Fleisig et al’s study of underweight and overweight baseball throwing showed variations in arm kinetics, variations in angular velocities, and relatively small changes in body positions.…”
Section: Discussionsupporting
confidence: 84%
“…Fleisig et al’s study of underweight and overweight baseball throwing showed variations in arm kinetics, variations in angular velocities, and relatively small changes in body positions. These changes could be reflective of reasonable training modalities for pitchers ( Fleisig et al, 2017a ; Fleisig et al, 2017b ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fleisig has shown that if flaws are identified, there is potential to correct them in both amateur and professional athletes. Flaws earlier in the motion near front foot contact have a better chance of being corrected than flaws later in the motion near the time of ball release [35]. …”
Section: Mechanicsmentioning
confidence: 99%